Balneotherapy in the Treatment of Knee Osteoarthritis: A Controlled Study - Şule ŞAHİN-ONAT and Özlem TAŞOĞLU and Zuhal ÖZİŞLER and Fulya DEMİRCİOĞLU GÜNERİ and Neşe ÖZGİRGİN (Archives of Rheumatology, 2015)
Objectives: This study aims to evaluate the efficacy of combined balneotherapy and physical therapy compared to physical therapy alone in the treatment of patients with knee osteoarthritis. Patients and methods: Forty-six patients (10 males, 36 females; mean age 70.82±7.78 years; range 57 to 85 years) with knee osteoarthritis were included in this study. Patients were assigned as group 1 and 2. Patients in group 1 (n=27) were treated with physical therapy alone, while patients in group 2 (n=19) were treated with balneotherapy combined to the same physical therapy protocol. All patients had physical therapy consisting of hot pack, transcutaneous electrical nerve stimulation, and ultrasonography for knee region, 45 minutes per day, five days a week for a total duration of three weeks. On the other hand, patients in group 2 also had daily balneotherapy sessions lasting 20 minutes, five days a week, again for three weeks duration. The demographic data and clinical features of the patients were recorded. Sickness impact profile was used for the evaluation of disease severity. Evaluation parameters also included visual analog scale, Western Ontario and McMaster Universities Arthritis Index, 10-meter walking test, and the use of analgesic drugs. Tests were performed both at baseline before treatment and at the end of the third week after treatment. Results: There were no significant differences between the two groups in terms of socio-demographic features. In both groups, significant improvements were observed for all of the measured variables (all p values <0.01). Moreover, group 2 had significantly superior improvements in all of the parameters compared to group 1 (all p values <0.05). Conclusion: Combined balneotherapy and physical therapy seems to be more effective in advanced knee osteoarthritis for improving pain, physical function and walking speed, compared to physical therapy alone.